Role of helix thickness in the field analysis and characterisation of the slow-wave structure of a broadband TWT - Ghosh S.; Jain P.K.; Basu B.N. (My University, 2025)
Considering the need to include the helix wire / tape thickness as a parameter of practical relevance in the analysis of a slow-wave structure of a broadband travelling-wave tube, a physical model for the actual helix is proposed in this paper. In this model, which combines the basic features of the two previously developed models for this purpose, the actual helix is replaced by two infinitesimally thin helically conducting sheaths at the inner and mean helix radii, respectively, between which the fields are made to remain constant. The field-analytical results for the phase velocity and impedance characteristics of the structure obtained using this model differ, in general, from those obtained by the previous models but pass on to latter as special cases. The study of the helix thickness effect based on this model shows that the helix becomes increasingly loaded i.e., the phase velocity of the structure decreases, as the envelope is brought closer to the helix, a larger permittivity helix support is used and the helix pitch angle is decreased. The effect is, however, found to be less pronounced for thicker helices. Furthermore, the control of the shape of the dispersion curve by structure parameters, say, to obtain a negative dispersion for a broadband TWT is lost if one increases the helix thickness, though the latter itself becomes a parameter for dispersion control. The effects of varying the structure parameters on its interaction impedance are also studied. The value of the interaction impedance is found to fall with the increase of frequency, however, the rate of fall being reduced for thicker helices. The interaction impedance also decreases with the increase of closeness of the envelope, helix-support permittivity and helix pitch angle. Moreover, the loaded helical structure behaves more like an unloaded structure (helix in free-space) as the helix thickness is increased. Since the helix thickness as a parameter controls the shape of the dispersion characteristics at a reasonably high interaction impedance value of the structure, the parameters could be used as an additional design parameter for wideband travelling-wave tube. © 1997 Taylor & Francis Group, LLC.